2002
DOI: 10.1177/0145482x0209600605
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Nonvisual Methods for Presenting Scientific Graphs

Abstract: In this research we implemented three different methods for presenting scientific graphs to blind and visually impaired people. Each rendering method employed either audition, kinesthetic or a combination of those two modalities. In order to allow for distance learning, we have used low cost portable devices for the output graph rendering. The three modes of representation were then compared by three separate groups of blind and visually impaired computer users. Each group consisted of four participants. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Mixed results in terms of a preferred mode of feedback were also found in [19]. Yu et al, however, did find that multilmodal (haptic and auditory) representation can enhance a user's ability to interpret graphs using a force feedback device in some cases [30].…”
Section: Point/coordinate Location Resultsmentioning
confidence: 99%
“…Mixed results in terms of a preferred mode of feedback were also found in [19]. Yu et al, however, did find that multilmodal (haptic and auditory) representation can enhance a user's ability to interpret graphs using a force feedback device in some cases [30].…”
Section: Point/coordinate Location Resultsmentioning
confidence: 99%
“…They also found that more disperse scatterplots were more difficult to accurately match to their visual representations. Roth et al [2002] found that participants had great difficulty (only a 25% rate of success) at identifying an auditory line graph as linear increasing; most participants mistook this function for a parabola. Performance for identifying auditory representations of parabola and sine wave functions was better (both had 75% rates of success).…”
Section: Complexity Of Graphical Displaysmentioning
confidence: 97%
“…Although auditory graph researchers have investigated auditory scatterplots [Bonebright et al 2001;Flowers et al 1997], box-whisker plots [Flowers and Hauer 1992;Lane 2003, 2005], histograms [Flowers and Hauer 1993], and tabular data [Stockman et al 2005], the majority of auditory graph research has examined auditory line graphs [Bonebright et al 2001;Brewster and Murray 2000;L. M. Brown et al 2002;Flowers and Hauer 1995;Mansur et al 1985;Roth et al 2002;Walker 2002, 2005;Turnage et al 1996;Walker and Nees 2005b]. This is not surprising, considering that line graphs accounted for 72.5% of graphs appearing in academic journals and 50.1% of all graphs appearing in newspapers in the sample obtained by Zacks et al [2002].…”
Section: The Current Researchmentioning
confidence: 99%
“…Many researchers [Fritz and Barner 1999;Jay et al 2008;Sjostrom et al 2003] propose the use of a magnetic force to pull the user towards the desired virtual object. In the work of Roth et al [2002], virtual fixtures and vibrations are used to haptically render line charts. Fritz and Barner [1999] use a light force to present the axes and gridlines.…”
Section: Audio Presentationmentioning
confidence: 99%